Pectus carinatum - Dogra, BB B; Dogra, BB B; Manmohan, Singh; Vijay, Langer (Indian Journal of Plastic Surgery, 2005)
Pectus carinatum is an uncommon congenital anomaly. Surgical correction for the deformity is infrequently sought but is usually very rewarding. There are three types of the deformity, viz. chondro- gladiolar, chondro-manubrial and the lateral variety, of which the latter is the most rare. We present a fifteen year girl who had pectus carinatum of the lateral variety involving the left second to the eighth costo-chondral junctions. The indication for surgical intervention was purely aesthetic. Subperichondrial excision of the lateral halves of the affected costal cartilages and shaving of the adjacent ribs was done. The post-operative recovery was uneventful and the deformity was corrected satisfactorily.
Keywords: Congenital; Thoracic wall; Abnormalities